2016
DOI: 10.1158/0008-5472.can-16-0485
|View full text |Cite
|
Sign up to set email alerts
|

Incipient Melanoma Brain Metastases Instigate Astrogliosis and Neuroinflammation

Abstract: Malignant melanoma is the deadliest of skin cancers. Melanoma frequently metastasizes to the brain, resulting in dismal survival. Nevertheless, mechanisms that govern early metastatic growth and the interactions of disseminated metastatic cells with the brain microenvironment are largely unknown. To study the hallmarks of brain metastatic niche formation, we established a transplantable model of spontaneous melanoma brain metastasis in immunocompetent mice and developed molecular tools for quantitative detecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
126
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(132 citation statements)
references
References 49 publications
6
126
0
Order By: Relevance
“…Recent studies documented an intensive reciprocal crosstalk between tumor cells and resident brain cells that principally determines the survival of a tumor cell and it's outgrowth as a macrometastasis in the brain [4, 8, 30]. Our results also showed, irrespective of the negative astrocyte effect on cancer cell proliferation, interaction of glial cells with tumor cells induces a more aggressive phenotype, as indicated by increased migration and invasion.…”
Section: Discussionsupporting
confidence: 70%
“…Recent studies documented an intensive reciprocal crosstalk between tumor cells and resident brain cells that principally determines the survival of a tumor cell and it's outgrowth as a macrometastasis in the brain [4, 8, 30]. Our results also showed, irrespective of the negative astrocyte effect on cancer cell proliferation, interaction of glial cells with tumor cells induces a more aggressive phenotype, as indicated by increased migration and invasion.…”
Section: Discussionsupporting
confidence: 70%
“…Immune surveillance in these host tissues eliminates a majority of the infiltrated cells and selects for cancer cells that evade immunity by entering quiescence or by other means (Malladi et al, 2016). Under the selective pressure of the microenvironment, metastasis initiating cells develop traits for the cooption of stromal components including osteoclasts in the bone marrow (Kakonen et al, 2002; Kang et al, 2003; Waning and Guise, 2014), macrophages, monocytes and neutrophils in the lungs (Acharyya et al, 2012; Chen et al, 2011; Qian et al, 2011; Wculek and Malanchi, 2015), and astrocytes in the brain parenchyma (Chen et al, 2016; Schwartz et al, 2016; Zhang et al, 2015). In sharp contrast to this paradigm, metastatic cells that enter the CSF confront an acellular environment that is relatively poor in nutrients and growth supporting signals.…”
Section: Discussionmentioning
confidence: 99%
“…Further contributing factors include the unique immune surveillance of the central nervous system (CNS) and the strict regulation of peripheral immune cell access. Likewise, we have demonstrated that astrocytes and microglia can foster the infiltration of metastatic cells into the brain parenchyma by serving as cellular guidance structures or active transporters (Chuang, van Rossum, et al, 2013;Pukrop et al, 2010;Rietkotter et al, 2013;Schwartz et al, 2016). This CNS-specific defense system, which consists of organ-resident microglia and astrocytes, is usually very effective and prevents the recruitment of peripheral immune cells, such as granulocytes and T cells that typically aggravate the situation by causing increased inflammation and tissue damage.…”
Section: Introductionmentioning
confidence: 92%